Optical Characterization of Transmitted Visible Photoluminescence of Bragg‐resonanced Porous Silicon. (17th January 2018) - Park, Mi‐Ae; Kim, Jin Soo; Cho, Soo Gyeong; Sohn, Honglae
Abstract : The investigation and optical characterization of Bragg resonance luminescence porous silicon (BRL PS) exhibiting both optical reflectivity and sharp photoluminescence (PL) at the Bragg resonance wavelength were reported. Two types of Bragg reflector porous silicon (BR PS) samples which exhibit strong reflection in visible or near infrared region and broad red PL were fabricated. When the Bragg reflection wavelength places in the range of emission wavelength, BR PS starts to exhibit narrowing of PL behavior. The optimization of Bragg resonance phenomenon of PL to generate sharp Bragg‐resonated PL by changing the number of repeats of Bragg‐stack layers. BR PS showing the reflection wavelength of 640 nm with 50 repeats exhibited sharp PL at the Bragg resonance wavelength with broad weak PL. BRL PS having 70% porosity with 1.45 refractive index displayed the second‐order reflectivity peak at 640 nm, thus sharp PL peak at 640 nm was the second‐order transmitted and amplified PL peak at the Bragg resonance wavelength. The optical properties of free‐standing BR PS film were investigated. The front side surface of BR PS shows both reflectivity and PL, however the back side surface of free‐standing BR PS shows only reflectivity without PL. Abstract :